THEORETICAL STUDY OF PRIORITY TECHNICAL AND TECHNOLOGICAL INDICATORS OF DRILLING RIGS IN THE CONTEXT OF THE MINING INDUSTRY OF THE REPUBLIC OF UZBEKISTAN - KHAYITOV, ODILJON; GULMURADOV, JAVOKHIR; KARAMOV, ALISHER; KUTTYBAYEV, AIDAR; SHVETS, YEHOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The purpose of this study is to analyze the technical efficiency and other technological characteristics of SBSH drilling rigs, which are widely used in the open-pit mining industry of the Republic of Uzbekistan, and to compare them with the modern Epiroc Pit Viper 231E drilling rig. The useful work coefficient of drilling machines in the mining industry is determined by the depth of the wells they drill (drill wells) and is called work efficiency. Drilling ability and other technical parameters are carried out through theoretical calculations.The study also aims to identify the necessary factors for the extensive utilization and validation of these rigs. The core of the work focuses on assessing the technical performance and drilling efficiency of SBSH-250 drilling rigs, followed by a technical analysis and comparison with the Epiroc Pit Viper 231E drilling rig, which meets similar technical requirements. Additionally, the superior capabilities of modern rigs, particularly the Epiroc Pit Viper 231E, are highlighted, emphasizing their advantages over traditional rigs such as the SBSH series. Considering all factors, the introduction of advanced technologies like the Epiroc Pit Viper 231E is expected to significantly enhance the production capacity of open-pit mining enterprises in the Republic of Uzbekistan. The extensive use and practical implementation of the Epiroc Pit Viper 231E drilling rigs, in particular, result in significantly higher efficiency. This technology allows for precise control over both productivity and worker safety. Furthermore, the remote-control system of the Epiroc Pit Viper 231E offers a strong incentive for reducing key operational costs.
Keywords: drilling rigs; technical productivity; axial force; rotary torque; сommon automation panel (CAP); Rig Control System (RCS); rock drilling index